Inadequate Funding of Basic Education in Nigeria: Implications for Quality and Equity in Learning Delivery - Adesola Afusat Odukoya; Egbedi Tungbowei (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractBasic education forms the cornerstone of national development, yet Nigeria continues to suffer from chronic underfunding despite policy frameworks aimed at universal access. This paper adopts a systematic literature review (SLR) methodology, guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, to investigate the implications of inadequate funding on the quality delivery of basic education in Nigeria. Drawing on peer-reviewed literature, policy documents, and empirical reports published between 1999 and 2024, the review sourced data from Google Scholar, JSTOR, ERIC, and ResearchGate. One thousand three hundred fifteen records were identified, with 86 studies meeting the inclusion criteria after screening and eligibility assessment. The findings highlight a consistent failure to meet the UNESCO-recommended 15–20% budgetary allocation for education, with basic education often receiving marginal and delayed disbursements. Key issues identified include dilapidated infrastructure, a shortage of qualified teachers, inadequate teaching materials, and weak financial accountability at the state level—aggravated by the conditional requirement for counterpart funding to access federal grants. The review also reveals that political apathy, poor fiscal planning, and mismanagement undermine efforts to improve basic education outcomes. The paper recommends a stronger policy enforcement mechanism, transparent fund allocation, and integrating alternative funding strategies such as public-private partnerships and community-based financing to reverse these trends. This review contributes valuable insights for policymakers and education stakeholders committed to achieving equitable and quality basic education in Nigeria by 2030.Keywords: basic education, educational underfunding, quality education delivery, nigeria education policy. AbstrakPendidikan dasar merupakan landasan pembangunan nasional, namun Nigeria terus mengalami kekurangan dana kronis meskipun kerangka kebijakan ditujukan untuk akses universal. Penelitian ini mengadopsi metodologi tinjauan pustaka sistematis (SLR), yang dipandu oleh kerangka PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), untuk menyelidiki implikasi dari pendanaan yang tidak memadai pada kualitas penyampaian pendidikan dasar di Nigeria. Mengacu pada literatur yang ditinjau sejawat, dokumen kebijakan, dan laporan empiris yang diterbitkan antara tahun 1999 dan 2024, tinjauan tersebut mengambil data dari Google Scholar, JSTOR, ERIC, dan ResearchGate. Seribu tiga ratus lima belas catatan diidentifikasi, dengan 86 studi memenuhi kriteria inklusi setelah penyaringan dan penilaian kelayakan. Temuan tersebut menyoroti kegagalan yang konsisten untuk memenuhi alokasi anggaran 15–20% yang direkomendasikan UNESCO untuk pendidikan, dengan pendidikan dasar sering kali menerima pencairan yang marjinal dan tertunda. Masalah utama yang diidentifikasi meliputi infrastruktur yang rusak, kekurangan guru yang berkualifikasi, materi pengajaran yang tidak memadai, dan akuntabilitas keuangan yang lemah di tingkat negara bagian—diperburuk oleh persyaratan bersyarat untuk pendanaan pendamping guna mengakses hibah federal. Tinjauan tersebut juga mengungkap bahwa apatisme politik, perencanaan fiskal yang buruk, dan salah urus melemahkan upaya untuk meningkatkan hasil pendidikan dasar. Penelitian ini merekomendasikan mekanisme penegakan kebijakan yang lebih kuat, alokasi dana yang transparan, dan mengintegrasikan strategi pendanaan alternatif seperti kemitraan publik-swasta dan pembiayaan berbasis masyarakat untuk membalikkan tren ini. Tinjauan ini memberikan wawasan berharga bagi para pembuat kebijakan dan pemangku kepentingan pendidikan yang berkomitmen untuk mencapai pendidikan dasar yang adil dan berkualitas di Nigeria pada tahun 2030.                      Kata kunci: pendidikan dasar, kurangnya dana pendidikan, penyediaan pendidikan bermutu, kebijakan pendidikan Nigeria.